2019
DOI: 10.7759/cureus.4002
|View full text |Cite
|
Sign up to set email alerts
|

To Choose or Not To Choose: Evaluating the Effect of a Choosing Wisely Knowledge Translation Initiative for Imaging in Low Back Pain by Emergency Physicians

Abstract: Introduction: We aimed to quantify the baseline familiarity of emergency medicine (EM) physicians with the Choosing Wisely Canada (CWC)-EM recommendations. We then assessed whether a structured knowledge translation (KT) initiative affected awareness, knowledge, and practice patterns for imaging in low back pain. Methods: We completed a two-center, before and after practice evaluation study. Physicians working in two Canadian emergency departments (EDs) were asked to participate in a survey before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…The most commonly targeted patient diagnosis was bronchiolitis [ 48 , 90 , 104 , 112 , 119 ], pulmonary embolism [ 49 , 58 , 60 , 82 , 100 , 102 , 121 , 122 , 125 ], and head injuries [ 67 , 70 , 77 , 79 , 87 , 94 , 101 , 123 , 126 , 127 ]. In studies targeting these complaints, a reduction in use of low-value imaging were reported in 78–80% of the studies, while imaging in lower back pain [ 38 , 45 , 51 , 53 , 54 , 65 , 68 , 71 , 75 , 89 , 115 , 118 ] were reduced in 58% of studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most commonly targeted patient diagnosis was bronchiolitis [ 48 , 90 , 104 , 112 , 119 ], pulmonary embolism [ 49 , 58 , 60 , 82 , 100 , 102 , 121 , 122 , 125 ], and head injuries [ 67 , 70 , 77 , 79 , 87 , 94 , 101 , 123 , 126 , 127 ]. In studies targeting these complaints, a reduction in use of low-value imaging were reported in 78–80% of the studies, while imaging in lower back pain [ 38 , 45 , 51 , 53 , 54 , 65 , 68 , 71 , 75 , 89 , 115 , 118 ] were reduced in 58% of studies.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 77 studies that reported improvements following the intervention [ 37 45 , 47 49 , 52 , 53 , 56 , 57 , 59 , 60 , 62 64 , 67 , 69 , 71 81 , 83 , 85 90 , 92 106 , 108 117 , 120 123 , 125 , 128 131 ], decreases in low-value imaging varied largely from < 1 to 62%. Of the remaining studies, three studies reported mixed results, where only some of the targeted low-value imaging examinations were reduced [ 46 , 54 , 68 ], and 16 studies showed a non-significant change or increase in the use of low-value imaging post-intervention [ 50 , 51 , 55 , 58 , 61 , 65 , 66 , 70 , 82 , 84 , 91 , 107 , 118 , 119 , 124 , 127 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps more time to mentally process the information (instead of immediately before their consultation) would lead to greater advocacy for high-value care. While education has been targeted at clinicians with mixed results in the past [ 25 ], the clinicians in our trial were blinded to the treatment arm and entire educational component for the duration of the study. It is possible that some providers adapt to routines for managing specific conditions, where passive patient personalities are less likely to challenge any decisions made by clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 130 patients, 89% reported learning many of their misconceptions about back pain from previous health care providers, which provides some insight as to why these beliefs are so difficult to unravel [ 22 ]. Mass media campaigns that leverage psychosocial paradigms to improve the public’s health literacy related to misconceptions about the biomedical causes of back pain have been called for [ 23 ], but the magnitude of their effect is questionable leaving room for improvement [ 24 , 25 ]. Focusing on the individual patient at the point of care with a more engaging format, right when the problem is most pressing, could provide another influential opportunity for education.…”
Section: Introductionmentioning
confidence: 99%